'Raising the bar' of patentability. (March 2012) - Atkinson, Jonathan; Jones, Rachel
The EPO has faced the public perception that the barrier to patenting is too low and that patent quality has deteriorated. With this in mind, the EPO has initiated a process of strategic renewal called 'raising the bar' with a view to improving the quality of patents and streamlining the grant procedure. This article discusses the changes to the European Patent Convention rules and how these changes aim to improve the quality of granted European patents.